Precursory deformation responses in different directions to catastrophic failure of uniaxially compressed sandstones - Cheng, L.; Hao, S.; Lu, C. (Archives of Mechanics, 2024)
The precursory acceleration of deformation is widely validated as a method for predicting the failure time. Damage evolution inside rocks generally results in complex strain patterns in the vicinity of failure and various responses of deformation in different directions. However, it is still unclear what the differences and similarities are during the evolution of strain components. In this paper, we compare the evolving properties of strain components in different directions based on experiments of sandstones under uniaxial compression. It is shown that the temporal patterns of vertical strains are much more complex in spatial distributions than that of horizontal strains. The horizontal strain presents two kinds of time courses characterized by precursory accelerations in both the strain localized zone and its surrounding areas, and the evolution without accelerations in positions is far from the strain localized zone. However, the vertical strain components corresponding to loading direction present complex evolving patterns with five kinds of time courses. The final amplitudes of horizontal strains are much higher than vertical components. Horizontal strains follow the power law acceleration with the well-defined exponents, but the exponents for vertical components are more scattered. Thus, horizontal strains can be applied to predict the failure time.